Methodology for three-dimensional analysis of asymmetries in joint moments in cycling - Martín-Sosa, Ezequiel; Mayo, Juana; Ojeda, Joaquín (Frontiers in Bioengineering and Biotechnology, 2026)
Background and introductionThe assessment of lower-limb joint moment asymmetries during cycling is critical, as inter-limb imbalances may lead to performance decrements, overload, or injury risk. While most investigations have focused on the sagittal plane, asymmetries may also arise in the frontal and transverse planes, with potential implications for both performance and health. The present study performed a three-dimensional analysis of joint moment asymmetries and examined the influence of pedalling power on their magnitude in ten amateur cyclists under three power conditions. Methodology Asymmetries were quantified using a modified version of the Normalised Symmetry Index (NSI), the Cross-Correlation Coefficient (CCC), and the newly proposed metric Asymmetries During Cycle (ADC) index.ResultsResults indicated that these indices must be applied jointly to identify whether asymmetries arise from magnitude differences, temporal pattern discrepancies, or both. The greatest asymmetries were observed in the frontal and transverse planes, and their magnitude decreased progressively with increasing pedalling power. DiscussionThe novelty of this work resides in the combined application of NSI, CCC, and the ADC index to three-dimensional joint moment analysis, which together provide a comprehensive and mechanistic understanding of asymmetries throughout the pedalling cycle, an approach not previously reported in cycling biomechanics.